KARAKTERISTIK KEGIATAN KEBUDAYAAN PARIWISATA DAN STRATEGI PENGUATAN TATA KELOLA DATA KEBUDAYAAN DI D.I. YOGYAKARTA - Ristanti; Tri Eko Yudiandri; Natalia Heni Primawarti (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2026)
This study aims to identify the characteristics of cultural activities and formulate strategies for strengthening cultural data governance in Daerah Istimewa Yogyakarta. The research employed a mixed-methods approach by combining descriptive qualitative analysis with strategic SWOT analysis. Primary data were collected through interviews, limited observation, and focus group discussions, while secondary data were obtained from policy documents, regional development reports, cultural activity archives, and official government publications. The results show that cultural activities in Daerah Istimewa Yogyakarta are predominantly concentrated in three major categories: cultural event development, capacity building for cultural human resources, and cultural infrastructure development. Among these categories, cultural events represent the most dominant type of program, indicating that public cultural activities remain the primary orientation of regional cultural policy. The study also reveals that cultural data governance has not yet been fully integrated across regional institutions. Differences in reporting formats, classification systems, and documentation practices among government agencies have led to fragmented cultural data, limiting its effectiveness as a basis for policy evaluation and planning. SWOT analysis indicates that cultural data governance is positioned in Quadrant I, reflecting strong internal capacity supported by regional cultural authority, special funding allocation, and active cultural communities, while external opportunities are strengthened by digital government transformation. The priority strategies recommended include developing an integrated digital cultural database across regional institutions, establishing standardized cultural activity classifications, and improving institutional capacity in digital cultural documentation. These strategies are expected to strengthen evidence-based cultural policy and support sustainable cultural governance in Daerah Istimewa Yogyakarta.